2021
DOI: 10.1111/ans.16742
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing post‐operative prophylactic anticoagulation in reconstructive head and neck cancer patients: a review

Abstract: Microsurgical reconstructive head and neck cancer patients are at high risk of venous thromboembolism. The use of anticoagulation can reduce their risk; however, this also increases their bleeding risk. It is not clear whether the benefits of treatment outweigh the risks, and whether a specific post-operative anticoagulation regime is superior. The aim of this review is to evaluate the evidence pertaining to the risks and benefits of post-operative anticoagulation and to provide a rationale for its use in head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…[39][40][41] As anticoagulation must be finely balanced with bleeding risk, use of anticoagulants must be tailored to suit unique patient needs, and risk stratification models exist to help providers make this decision. 42 Patients with coexisting coagulopathies (ie, hemophilia, von Willebrand's disease, thrombocytopenia, liver disease) may therefore benefit from an individualized approach to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] As anticoagulation must be finely balanced with bleeding risk, use of anticoagulants must be tailored to suit unique patient needs, and risk stratification models exist to help providers make this decision. 42 Patients with coexisting coagulopathies (ie, hemophilia, von Willebrand's disease, thrombocytopenia, liver disease) may therefore benefit from an individualized approach to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…60 On the other hand, Cevik et al, in a review of 306 studies and meta-analysis of nine studies of head and neck microsurgical patients showed that anticoagulation lowers the risk of VTE in this patient group, but also increases the bleeding risk, necessitating risk stratification using the Caprini RAM to make decisions. 61 Based on their metaanalysis, LMWH appeared to be superior to heparin when was given twice daily but equal to heparin three times daily with similar complication profile in cancer patients. 61 Chien et al in a retrospective study on 216 patients who underwent head and neck microvascular reconstruction showed that combination of SQH (5,000 U twice daily) and ASA (325 mg orally daily) does not have significant effect on hematoma rate (5.6% vs. 5.3%).…”
Section: Head and Neck Microvascular Reconstructionmentioning
confidence: 99%
“…61 Based on their metaanalysis, LMWH appeared to be superior to heparin when was given twice daily but equal to heparin three times daily with similar complication profile in cancer patients. 61 Chien et al in a retrospective study on 216 patients who underwent head and neck microvascular reconstruction showed that combination of SQH (5,000 U twice daily) and ASA (325 mg orally daily) does not have significant effect on hematoma rate (5.6% vs. 5.3%). 62 In a prospective study Ambani et al studied 90-day postoperative VTE and bleeding events in 78 patients who underwent free tissue reconstruction following tumor resection for head and neck or breast cancer.…”
Section: Head and Neck Microvascular Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations